Ferroptosis in Intrahepatic Cholangiocarcinoma: IDH1105GGT Single Nucleotide Polymorphism Is Associated With Its Activation and Better Prognosis - Sarcognato, Samantha; Sacchi, Diana; Fabris, Luca; Zanus, Giacomo; Gringeri, Enrico; Niero, Monia; Gallina, Giovanna; Guido, Maria (Frontiers in Medicine, 2022)
Objectives Intrahepatic cholangiocarcinoma (ICC) has a dismal prognosis and often demonstrates an anti-apoptotic landscape, which is a key step to chemotherapy resistance. Isocitrate dehydrogenase 1 or 2 (IDH1-2)-mutated ICCs have been described and associated with better prognosis. Ferroptosis is a regulated iron-mediated cell death induced by glutathione peroxidase 4 (GPX4) inhibition, and may be triggered pharmacologically. GPX4 is overexpressed in aggressive cancers, while its expression is inhibited by IDH1R132C mutation in cell lines. We investigated tissue expression of ferroptosis activation markers in ICC and its correlation with clinical-pathological features and IDH1-2 status. Materials and methods We enrolled 112 patients who underwent hepatic resection or diagnostic liver biopsy for ICC. Immunostaining for transferrin-receptor 1 and GPX4, and Pearls’ stain for iron deposits were performed to evaluate ferroptosis activation. Immunostaining for STAT3 was performed to study pro-inflammatory and anti-apoptotic landscape. Main IDH1-2 mutations were investigated in 90 cases by real-time polymerase chain reaction. Results GPX4 overexpression was seen in 79.5% of cases and related to poor histological prognostic factors (grading and perineural and vascular invasion; p<0.005 for all) and worse prognosis (OS p = 0.03; DFS p = 0.01). STAT3 was expressed in 95.5% of cases, confirming the inflammation-related anti-apoptotic milieu in ICC, and directly related to GPX4 expression (p <0.0001). A high STAT3 expression correlated to a worse prognosis (OS p = 0.02; DFS p = 0.001). Nearly 12% of cases showed IDH1105GGT single nucleotide polymorphism, which was never described in ICC up to now, and was related to lower tumor grade (p <0.0001), longer overall survival (p = 0.04), and lower GPX4 levels (p = 0.001). Conclusions Our study demonstrates for the first time that in most inflammatory ICCs ferroptosis is not active, and its triggering is related to IDH1-2 status. This supports the possible therapeutic role of ferroptosis-inducer drugs in ICC patients, especially in drug-resistant cases.